A novel mobile transtelephonic system with synthesized 12-lead ECG. - Hadzievski, L. (IEEE Transactions on information technology in biomedicine)
The problem of synthesizing the standard 12-lead electrocardiogram (ECG) from the signals recorded using three special ECG leads is studied in detail. The implementation of that concept into the design of a new mobile ECG transtelephonic system is presented. The system has two separate units: a stationary diagnostic-calibration center and a mobile ECG device with integrated electrodes. The patient records by himself three special leads with the mobile ECG recorder and sends data via cellular phone to the personal computer in the diagnostic center where standard 12-lead ECG is numerically reconstructed on the base of the patient transformation matrix previously calculated into the calibration process. The experimental study shows high accuracy of the reconstructed ECG.